Mathematics and statistics for an international economist: some elements of Calculus - Khomyak, Maria (Lesya Ukrainka Volyn National University, 2024)
The methodological recommendations are given curriculum for the discipline "Mathematics and statistics for an international economist" of the professional training of the bachelor of specialty 292 International Economic Relations. The methodological recommendations contain some specific topics from Calculus of the course Mathematics and statistics for an international economist. For each of the topics typical examples along with their solutions are considered. They could be useful in preparation for practical classes as well as the independent work and also for quizzes and the final exam.
Keywords: 517(076)